Some initial comments of geological environment change when exploiting brown coal in Bac Bo plain - Tu, Tran Van (Vietnam Journal of Earth Sciences, 2014)
Using the finite element method to determine the stress concentration around the tunnel and land surfacesubsidence due to exploiting brown coal. This is a modern and effective method compared with the results calculatedfrom observations in mining. However, with the current limited documentation on network geological survey andexperimental rock mechanics. This is only meaningful initial results refer to the study of geological environmental changesurrounding brown coal mining in the Bac Bo delta. The geological environment changes due to brown coal mining underBac Bo Delta can list, (1) ground subsidence can cause distortion and fracture of traffic and building constructions,especially dam system; (2) significantly decreased the water table in the area, causing pollution to groundwater and thesecondary ground deformation, and affects crops in the region; (3) the impact increased diversion of the Red River-bedby a neighbouring natural imbalance. Besides, there are a variety of different social implications for brown coal miningunder the Red River Delta where has a long time of culture of the nation and this is also where the socio-economic focusof Vietnam. However in the future energy balance, the exploitation of this fuel obliges to proceed. With advances inscience and technology especially coal mining technology, is necessary to minimize the adverse effects mentionedabove. Results of calculation show that the level of major subsidence and accounting for a wide range of land surface bybrown coal mining. Especially the decline in ground water due to dry off in the process of exploiting mines have changedreally geological environment and a very large impact on people’s living and food production in the region. Although thegovernment has to change the purpose of land use. This paper shows some results for managers, scientists furtherreview to determine the time of brown coal mining in the future and provide the rational exploitation of technology. References Phùng Mạnh Đắc (chủ biên), 2006. Nghiên cứu các giải pháp khoa học và công nghệ nhằm huy động tổng hợp tài nguyên phục vụ cho chiến lược phát triển bền vững trong khai thác và sử dụng than ở Việt Nam. Chương trình trọng điểm của Bộ Công nghiệp 2001-2005. Lưu trữ tại Tổng công ty Than và KS Việt Nam. Trần Văn Tư, 1989. Nghiên cứu phân bố ứng suất và biến dạng xung quang đường hầm trong môi trường đá phân lớp, biến dạng phi tuyến. Luận án PTS KHKT, Lưu trữ tại Thư viện Quốc gia Hà Nội. Trần Văn Tư (chủ biên), 2009. Đánh giá sự biến dạng bề mặt đất và công trình do hoạt động tự nhiên và kinh tế khu vực thành phố Hà Đông và lân cận - tỉnh Hà Tây. Đề tài cấp thành phố Hà Nội. Lưu trữ tại Sở KH & CN Hà Nội. Đoàn Thế Tường, 1999. Dự báo khả nănglún bề mặt đất do hạ thấp mực nước ngầm. Báo cáotổng kết đề tài RD 9505. Lưu trữ tại Sở KH & CNH à Nội. Tổng Công ty Than Việt Nam, 2003. Báo cáo địa chất kết quả khảo sát, tìm kiếm, thăm dò than đồng bằng sông Hồng, vùng Bình Minh, Khoái Châu, Hưng Yên. Lưu trữ tại Tổng công ty Than và KS Việt Nam.